2017
DOI: 10.1158/1940-6207.capr-17-0125
|View full text |Cite
|
Sign up to set email alerts
|

Circulating RANKL and RANKL/OPG and Breast Cancer Risk by ER and PR Subtype: Results from the EPIC Cohort

Abstract: Receptor activator of nuclear factor kappa-B (RANK)-RANK ligand (RANKL) signaling promotes mammary tumor development in experimental models. Circulating concentrations of soluble RANKL (sRANKL) may influence breast cancer risk via activation of RANK signaling; this may be modulated by osteoprotegerin (OPG), the decoy receptor for RANKL. sRANKL and breast cancer risk by hormone receptor subtype has not previously been investigated.A case-control study was nested in the European Prospective Investigation into Ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 49 publications
(80 reference statements)
4
27
2
Order By: Relevance
“…Intra-batch coefficients of variation were 14.4% for sRANKL, and 15.3% for OPG. Within-person reproducibility of sRANKL and OPG over one and 14 years observed in our study have been published previously [ 9 , 12 ], Spearman correlation coefficients were r = 0.85 and r = 0.75 for OPG and r = 0.60 and r = 0.38 for sRANKL over one and 14 years, respectively.…”
Section: Methodssupporting
confidence: 88%
See 4 more Smart Citations
“…Intra-batch coefficients of variation were 14.4% for sRANKL, and 15.3% for OPG. Within-person reproducibility of sRANKL and OPG over one and 14 years observed in our study have been published previously [ 9 , 12 ], Spearman correlation coefficients were r = 0.85 and r = 0.75 for OPG and r = 0.60 and r = 0.38 for sRANKL over one and 14 years, respectively.…”
Section: Methodssupporting
confidence: 88%
“…We have previously shown that OPG concentrations are reproducible over one and 14 years ( r = 0.85 and r = 0.75 respectively) [ 9 ]. Reproducibility of sRANKL was lower ( r = 0.60 and r = 0.38 over one and 14-years, respectively) [ 12 ]. This indicates that a single sRANKL measurement may not be representative of longer-term exposure, and may lead to attenuation of risk estimates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations